Discourses of language acquisition and identity in the life histories of four white South African men, fluent in isiXhosa - Botha, Elizabeth Katherine (School of Education, 2018)
A post-structuralist framework (Foucault, 1976; Weedon, 1997) is used to explore language acquisition and identity construction in the life histories of four multilingual white South African men, who became fluent in the African language of isiXhosa in the racially-divided world of Apartheid South Africa, at a time when law and policy made fluency in an African language unusual for whites. Theories used within the 'social turn' in Second Language Acquisition (Block, 2003; Norton, 2000), as well as the social learning theory of Lave and Wenger (1991), support an exploration of how the men acquired this language on the farms in the Eastern Cape where they spent their early years. The identity implications of the men's multilingualism are examined using post-colonial studies of race, 'whiteness' and hybridity (Bhabha, 1994; Frankenberg, 1993; Hall, 1992a). The study was undertaken using Life History methodology (Hatch & Wisniewsky, 1995) and biographic interviewing methods developed within the Social Sciences (Wengraf, 2001). Poststructuralist discourse analysis (Wetherell & Potter, 1992), together with aspects of narrative analysis (Brockmeier, 2000), were used to analyse the data. The study contributes to research into naturalistic language acquisition, using theories from the 'social turn', and analysing a bilingual context in which language, power, race and identity interact in unique ways. The findings endorse the importance of a post-structuralist framing for the Communities of Practice model (Wenger, 1998), and show that participation in target-language communities requires investment by learners in identities which ameliorate the inequities of power relations. The study shows that isiXhosa can become linguistic capital (Bourdieu, 1991) for white South Africans, depending on context and the isiXhosa register they use. It demonstrates that Apartheid discourse ascribes to the men an identity which is indisputably white, but that early experiences shared with isiXhosa-speakers shape their lives and form a potentially antihegemonic facet of their identities.